TECHNOLOGIES FOR DEVELOPING AESTHETIC TASTE IN STUDENTS - Nazarova Gulshan Ismoilovna (New modern researchers: modern proposals and solutions, 2025)
This article discusses the importance of cultivating aesthetic taste among students, the key factors influencing aesthetic development, and the use of modern educational technologies in this process. It highlights interactive methods and interdisciplinary approaches that enhance the effectiveness of aesthetic education in schools.